PERLINDUNGAN HUKUM PADA NASABAH BANK ATAS SEBAGIAN DANA YANG HILANG AKIBAT KARTU ANJUNGAN TUNAI MANDIRI (ATM) YANG TERTELAN DALAM MESIN ATM BERDASARKAN UNDANG UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Samuel Adityananta (Perpustakaan Universitas Surabaya, 2014)
Existence of bank customers in important existing in this country, more over the number of banking businesses spend a lot of their banking products to advance economy this country. In addition to the importance of banking business, there is one thing that should not be forgotten inside the bank liable in case of loss to the customer. As experienced by the Mujahidin Tahir cleansed seeking accountability given by the Independent Bank.